2019
DOI: 10.1155/2019/9515628
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Are Dysregulated in Patients with Hereditary Angioedema Types I and II in a Symptom-Free Period

Abstract: Neutrophils impact on processes preceding the formation of bradykinin, a major swelling mediator in hereditary angioedema (HAE), yet their potential role in HAE pathogenesis has not been sufficiently studied. We assessed the relative mRNA expression of 10 genes related to neutrophil activation using RNA extracted from the peripheral blood neutrophils of 23 HAE patients in a symptom-free period and 39 healthy donors. Increased relative mRNA expression levels ofCD274,IL1B,IL1RN,IL8,MMP9, andTLR4, together with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 77 publications
(80 reference statements)
0
7
1
Order By: Relevance
“…We propose that the higher level of NGs in the symptom-free stage of the patients may contribute to the constant activation of the KKS [ 42 ]. In contrast to previous studies [ 14 , 45 ], we could not find any significant difference in IL-8 levels—one of the best-known chemotactic factors for NGs—between patients and healthy controls. Interestingly, we found that CCL5 and MCP-1 may have an important role in NG recruitment in HAE.…”
Section: Discussioncontrasting
confidence: 99%
“…We propose that the higher level of NGs in the symptom-free stage of the patients may contribute to the constant activation of the KKS [ 42 ]. In contrast to previous studies [ 14 , 45 ], we could not find any significant difference in IL-8 levels—one of the best-known chemotactic factors for NGs—between patients and healthy controls. Interestingly, we found that CCL5 and MCP-1 may have an important role in NG recruitment in HAE.…”
Section: Discussioncontrasting
confidence: 99%
“…NEAT1 and CD180 were upregulated and surprisingly IL1RN was also upregulated in patients with a severe phenotype compared to patients with a mild one. In our previous work (Grymová et al, 2019), we showed that CXCL8 expression was higher in HAE patients' neutrophils, while its plasma level was decreased. This discrepancy is now easily interpretable if we consider different CXCL8 resources in the plasma.…”
Section: Macrophages In Hae Coursementioning
confidence: 81%
“…Interestingly, CXCL8 and TNF- α levels, both involved in PMN activation and/or released by neutrophils, were also altered in C1-INH-HAE patients during acute phase compared with symptom-free period [ 63 ] (Table 1 ). Grymova and colleagues confirmed PMN activation and dysregulation in C1-INH-HAE type I and II patients [ 64 ]. mRNA expression of 10 genes related to PMN activation (CD274, IL1 β , IL1RN, CXCL8, MMP9, and TLR4) was increased in HAE patients in symptom-free periods compared with healthy donors in addition to increased CD11b, decreased CD16 plasma membrane deposition, and increased relative CD274 + and CD87 + neutrophil counts, but not by increased NE or MPO plasma levels (Table 1 ).…”
Section: Innate Immune Systemmentioning
confidence: 95%
“…mRNA expression of 10 genes related to PMN activation (CD274, IL1 β , IL1RN, CXCL8, MMP9, and TLR4) was increased in HAE patients in symptom-free periods compared with healthy donors in addition to increased CD11b, decreased CD16 plasma membrane deposition, and increased relative CD274 + and CD87 + neutrophil counts, but not by increased NE or MPO plasma levels (Table 1 ). In addition, a co-culture of PMN and T-cells/PBMC showed a suppressive function of patient’ PMN resulted from a decreased CD25 + and IFN- γ + T-cell/PBMC ratio in patients [ 64 ].…”
Section: Innate Immune Systemmentioning
confidence: 99%